2014
DOI: 10.15680/ijirset.2014.0309002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mixture, Wire Mesh and Thickness on the Flexural Performance of Hybrid PVA Fibre Ferrocement Panels

Abstract: This paper presents the results of an experimental investigation into the flexural performance of hybrid polyvinyl alcohol (PVA) fibre ferrocement (HFF) composites panels. The primary focus is on the influence of mixture matrix and wire mesh content in the panels which have different thicknesses. The effect of using fly ash and silica fume in the mixtures is investigated from the testing of 21 panels. Best performed mixes are then chosen to prepare additional 27 ferrocement panelswith varying thicknesses and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…and/or fibres, the higher the flexural load (or equivalent flexural strength) of HMFRCBC slab elements [41]. In a similar study, Abushawashi and Vimonsatit (2014) [42] used hybrid PVA fibre and steel wire mesh in fibrous ferrocement slab panels measuring 620 × 200 × 25 mm (thickness) with MVr=0.80% (3 mesh layers) and PVA Vf=1.5%, which showed first crack and ultimate deflection of 0.57 mm and 10.38 mm, respectively.…”
Section: Flexural Load and Deflectionmentioning
confidence: 79%
“…and/or fibres, the higher the flexural load (or equivalent flexural strength) of HMFRCBC slab elements [41]. In a similar study, Abushawashi and Vimonsatit (2014) [42] used hybrid PVA fibre and steel wire mesh in fibrous ferrocement slab panels measuring 620 × 200 × 25 mm (thickness) with MVr=0.80% (3 mesh layers) and PVA Vf=1.5%, which showed first crack and ultimate deflection of 0.57 mm and 10.38 mm, respectively.…”
Section: Flexural Load and Deflectionmentioning
confidence: 79%
“…The ductility ratio for ferrocement slabs tested under flexure showed the highest value of 1.77 in the case of F4MB1PPF-S and the least value of 1.16 for F1MC1PPF-S. The trend is increasing by increasing the percentage volume fraction (V r ) of reinforcement mesh [ 36 ]. Therefore, the presence of PPF inhibits intrinsic cracking in concrete.…”
Section: Resultsmentioning
confidence: 99%
“…The increased number of wire meshes distributed along the thickness of the slab resulted in more strength capacity and ductile behavior [ 34 ]. The optimization of the reinforcement wire contentled to a general increase in the flexural strength, ductility, tensile strength and energy dissipation capabilities [ 35 , 36 , 37 , 38 ]. The experimental results also concluded that 0.6% of superplasticizer along with 20% fly ash and 5% SF resulted in improved flexural performance in strength and toughness [ 39 ]…”
Section: Introductionmentioning
confidence: 99%